Following growth in the amount of organizations and winning some quality attributes of pomegranate cultivars Salimi and narrators of seedless - Baghdad Science Journal (مجلة بغداد للعلوم)
The research was conducted in the Department of Horticulture College of Agriculture, University of Baghdad for two seasons 1999-2000 on cultivars pomegranate Salimi and narrators seedless to study the effect of growth regulators in the amount of winning and some qualities included experience 9 transactions and three replicates per treatment used experience global Dhant design sectors full randomization carried out transactions in the two datesfirst at the onset of flowering and the second after 70 m results showed superior product Salimi Rawa